Efficacy of training and development in technological colleges in DakshinaKannada district - Raghavendran, V; Kumuthadevi, K (International Journal of Engineering and Technology, 2018)
Training and development are the vital steps and indicators in an incessant process of improving the quality of human resources. It is an endeavor to advance their existing and prospective performance. The institute should also keep a track on faculty’s achievements after imparting the indoctrination. It means that the training requires systematic evaluation. Training refers to a methodical procedure of shifting the actions/ behaviors of faculty’s in a path to attain the institution’s missions. An instruction courses is an exercise by the management to provide occasion for the faculty’s to acquire ability and inter-related dexterity, approach and information. In order to meet the end goals of education, the training segment has to become vibrant and refreshed updated in contemporary scenario. In order to take this training area to heights of intercontinental distinction, there is a requirement for the paramount amalgamation of new knowledge and dexterous capable labor pool. An investigation is explored through this research paper to learn the methodology of training and development in technological institutions in Dakshina Kannada District and its impact on generating efficiency among teachers to cater to the need of the students.